Estudio sobre los patrones de uso de antibióticos y los factores de relevancia en el surgimiento de la resistencia bacteriana en fincas lecheras artesanales de Costa Rica - Luna Tortós, Carlos (2006)
A survey on antibiotic use was carried out in 60 dairy farms located in Santa Cruz, Turrialba, Costa Rica, which were not subjected to official inspection for detection of drug residues. Several aspects regarding antibiotic use and factors related to the selection of resistant bacteria were included in the survey. Furthermore, some factors concerning milk handling and milk products elaboration, especially those influencing its microbiological quality, were studied. Concerning the hygienic quality of milk and milk products, 73% of farmers produce non-pasteurized, fresh cheese. The milk produced in 25% of farms is subjected to pasteurization. Over a half of the farmers milk the cattle manually. During pre-milking process most farmers wash the hind limbs, the udder and he nipples, whiles only 30% of farmers use separate towels to dry out the nipples. In relation to drug use, the group of drugs mostly indicated by farmers as frequently used was the antibiotics one. Penicillins, tetracyclines and aminoglycosides were the antibiotic groups with higher frequency of use. Penicillins are preferred for systemic antimicrobial therapies (any disease) and for dry-cow therapy (90% in both indications). Same percent of farmers (90%) use tetracyclines and aminoglycosides for systemic therapy (any disease). The aminoglycosides predominate in mastitis therapy (80%), and are the second group of choice for dry-cow therapy (73%). Novel cephalosporins are mainly used as anti-mastitis therapy (10%), while fluoroquinolones are mainly used as systematic antibiotic therapy (any disease, 15%). The present survey also determined the following patterns of antibiotic use: lack of objective diagnostic bases as fundament for antibiotic therapy; antibiotic without prescription. It is considered that the results of this survey will offer a base helping to develop new strategies that enable the prudent antibiotic se in these dairy farms.